Impact of Inflation and Consumer price index on Stock Market Return: A Case of Sri Lanka - Sobana, S.; Muraleetharan, P. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2024)
This study investigates the impact of inflation and the Consumer Price Index (CPI) on stock market returns in Sri Lanka from 2007 to 2021. Inflation and the CPI are used as independent variables, while the All Share Price Index (ASPI) serves as the dependent variable for analyzing the stock market in Sri Lanka. Inflation, a key macroeconomic variable, adversely affects the macroeconomic equilibrium of an economy. ASPI data was collected from the Colombo Stock Exchange (CSE) website, with a sample of 180 monthly observations. The objective of the research is to examine how inflation and the CPI influence stock market returns in the Sri Lankan context and to understand the potential implications of these variables on stock returns in the Sri Lankan capital market. The study employs both correlation analysis and a linear regression model. The results show that correlation analysis indicates a weak positive influence of the ASPI on inflation and the CPI. However, the regression model reveals a significant negative relationship between the ASPI and both inflation and the CPI.
Keywords: All share price index; Consumer price index; Inflation